Human Capital and Sustainable Transportation Strategic Alignment in Public Sector Enterprises - Taufiq Rahmat (Trasearch (Training, Research and Academy Society, 2025)
Public sector enterprises play a vital role in achieving national sustainability goals, particularly in the transportation domain. However, a persistent problem is the inadequate alignment between human capital development and the strategic implementation of sustainable transport policies. This misalignment often results in ineffective program delivery, limited innovation, and inefficient resource allocation. The purpose of this study is to explore how human capital is managed and strategically aligned with sustainable transportation objectives within public sector enterprises in Indonesia. Using a qualitative multiple-case study method, data were collected from 15 key informants across three levels of government—national, provincial, and municipal—through semi-structured interviews and document analysis. The findings indicate that institutions investing in targeted staff training, sustainability-focused leadership, and inter-agency collaboration tend to show stronger performance in implementing environmentally responsible transportation systems. Nonetheless, the study also identifies key barriers such as fragmented policy execution, lack of integrated performance evaluation, and limited institutional capacity. These insights underscore the importance of embedding environmental competencies and systems thinking within human capital strategies in the public sector. The study contributes theoretically by linking human capital theory to sustainable transportation and public sector innovation. Practically, it offers policy recommendations to improve workforce planning and capacity building aligned with long-term sustainability targets.